Implementasi Manajemen Sumber Daya Manusia Terhadap Peningkatan Mutu Di SMK Negeri 5 Lhokseumawe - Nasruddin Nasruddin; Sri Wahyuni; Sutan Febriansyah (Jurnal Visioner & Strategis, 2021)
This study aims to determine the effectiveness of the implementation of human resource management on improving the quality of schools in SMK Negeri 5 Lhokseumawe. The population in this study were all teachers and administrative staff at SMK Negeri 5 Lhokseumawe, as many as 36 people. The sampling method in this study used a saturated sample, where the entire population was sampled. The data used are primary data obtained by distributing questionnaires to respondents. The data were processed using the SPSS 18 program. The results showed that the implementation of human resource management and quality implementation at SMK Negeri 5 Lhokseumawe was categorized as good, with the percentage of respondents answering as much as 58% and 42%, respectively. This shows that SMK Negeri 5 Lhokseumawe has paid attention to and managed its human resources well in realizing quality education.Keywords: Human Resource Management, Quality Implementation,                       Implementation